GE_GERICHTE C/21301/2012 vom 3. Oktober 2014 - GE Cour de justice (2014)
CONTRAT DE TRAVAIL; LÉGITIMATION ACTIVE ET PASSIVE; DROIT AU SALAIRE; RÉSILIATION IMMÉDIATE; JUSTE MOTIF | CO.319; CO.320.2; CO.337; CTT-Edom; CC.166; CPC.227